Sudden Infant Death Syndrome: Definition Evolution, Epidemiology and Risk Factors - Natalya N. Korableva ("Paediatrician" Publishers LLC, 2021)
The literature overview about the issues of sudden infant death syndrome (SIDS) is presented in the article. The emphasis is on the evolution of the diagnosis definitions, incorrect use of the "synonym" term "sudden child death syndrome" in our country. Epidemiological characteristics of SIDS in countries with different levels of per capita income are presented. Modern view on the theories of the syndrome onset is analyzed. Risk factors are analyzed from the position of influence and change, i.e. possible modification to affect the syndrome incident that is crucial for every pediatrician. SIDS protective factors as the basis of primary prevention are discussed. The algorithm for organizing safe sleep space for children to reduce the risks of infant death associated with sleep is presented. This algorithm is proposed to be used in educational programs for pregnant women and parents of infants.